2018
DOI: 10.1080/15384101.2018.1480219
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Tat increases BAG3 via NF-κB signaling to induce autophagy during HIV-associated neurocognitive disorder

Abstract: The human immunodeficiency virus-1 (HIV-1) regulatory protein Tat plays an important role during HIV-1-associated neurocognitive disorders (HAND) by inducing neuronal autophagy. In this study, we used immunohistochemistry, immunofluorescence, western blot, qRT-PCR, and RNA interference to elucidate the involvement of Bcl-2-associated athanogene 3 (BAG3) in the pathogenesis of HIV-1 Tat-induced autophagy during HAND. We found that BAG3 expression is elevated in astrocytes in frontal cortex of macaques infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
(36 reference statements)
0
16
0
Order By: Relevance
“…Additionally, experiments performed in transgenic mice that specifically express HIV-1 Tat protein, have confirmed that transgenic mice without HIV-1 infection but expressing HIV-1 Tat exhibit similar recognition and behavioral changes as HAND patients (Kim et al, 2003). Furthermore, our former works have demonstrated that HIV-1 Tat may participate in the pathogenesis of HAND (Ye et al, 2017; Wu et al, 2018). Accordingly, we surmised that the expression of FOXO3 in neurons potentially regulated by HIV-1 Tat in HAND.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, experiments performed in transgenic mice that specifically express HIV-1 Tat protein, have confirmed that transgenic mice without HIV-1 infection but expressing HIV-1 Tat exhibit similar recognition and behavioral changes as HAND patients (Kim et al, 2003). Furthermore, our former works have demonstrated that HIV-1 Tat may participate in the pathogenesis of HAND (Ye et al, 2017; Wu et al, 2018). Accordingly, we surmised that the expression of FOXO3 in neurons potentially regulated by HIV-1 Tat in HAND.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of NFkB often acts as an initiating signal for the transcription of HIV-1, and targeting this signaling pathway could prevent ongoing low-level neurodegeneration by disturbing HIV-1's ability to sense immune cell activation [89]. Inhibition of NF-κB activity can reverse neuronal autophagy induced by Tat [90]. We recently reported that HIV-1 Vpr-induced proin ammatory response and apoptotic cell death are mediated through the NF-kB activation in astrocytes [91].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that Nef-protein, encoded by human immunodeficiency virus type 1 (HIV-1), blocks the fusion of the autophagosome with the lysosome, thereby keeping the virus inside cells [ 56 ]. Later, the virus found to encodes the protein Tat promote autophagy in neuronal cells [ 57 ] and gliomas via BAG3 signaling [ 57 ].…”
Section: Unfolded Protein Response (Upr): One Process Two Impactsmentioning
confidence: 99%